Useless Box: A Sonic Automaton Integrating Robotics, Sound Art, and Performance - Kokoras, Panayiotis (Anais do Simpósio Brasileiro de Computação Musical (SBCM); 2025: Anais Estendidos do XIX Simpósio Brasileiro de Computação Musical, 2025)
Useless Box is a transdisciplinary performance work at the intersection of robotics, sound art, and interactive composition. Inspired by the myth of Pandora’s Box and Schrödinger’s cat, this piece utilizes an autonomous wooden box equipped with physical computing, sensors, and actuators, all controlled by a MaxMSP-based system with machine listening and AI capabilities. Through the integration of sound design, theatricality, and algorithmic processes, Useless Box explores questions of agency, unpredictability, and performativity. The box, which initially appears empty and inert, unfolds into an unpredictable sonic and kinetic world—oscillating between reality and fantasy, mechanical and organic, the playful and the ominous. The work challenges conventional notions of instrumentality, composition, and performer/audience relationships by blurring the boundaries between object and subject, chaos and order, and the real and the imagined.